THE IMPLEMENTATION OF GROUP GUIDANCE TO REDUCE ACADEMIC PROCRASTINATION OF COLLEGE STUDENTS - Yulian Hermanus Wenno; Theophanny P.T. Rampisela, Fajrin A. Duila (Adisam Publisher, 2024)
This study aims to determine whether the implementation of group guidance using modeling techniques can affect the tendency of academic procrastination of students of the Pattimura University Guidance and Counseling Study Program, this research is located at Pattimura University, Ambon. The population amounted to 97 students using purpose sampling technique totaling 18 respondents. The research design used Pre- experimental One-Group Pretest-Posttest Design with Paired sample test data analysis techniques used to test the research hypothesis. Researchers also conducted validity, reliability and prerequisite tests. The results showed a difference in the average score before treatment and after with a paired sample t-test value of sig. 0.000 <0.05 which means Ho is rejected and Ha is accepted where the provision of group guidance treatment using the Modeling Technique has a significant effect on reducing student procrastination, although in the category is still in the moderate category.